Internalisasi Penerapan Bahasa Ibu Sebagai Alat Komunikasi Penunjang Dalam Pelaksanaan Proses Pembelajaran Di Mi Raudlatul Munadhirin Pandean - Yaqin, Firdaus Ainul; Puja Krisanti , Firmadani Eka (ELEMENTARY : Journal of Primary Education, 2023)
Most children who have just started school will have difficulty understanding Indonesian, especially for children who are in elementary school or elementary school. During the language acquisition period at the age of elementary school children, students will have two languages, namely their mother tongue and Indonesian. The language contact that occurs in a child creates a mutual influence between the mother tongue and Indonesian, the mutual influence between the mother tongue and Indonesian means that the mother tongue influences Indonesian, or vice versa. That way the communication between the teacher and here uses two languages ​​where students communicate using Indonesian while students use their mother tongue and Indonesian combined. Therefore this study aims to determine the use of mother tongue as a supporting communication tool in the learning process and also to know the role of mother tongue in supporting the learning process. This research was designed using a descriptive qualitative approach, with the type of Case Study Research, and was carried out in one of the Islamic elementary schools in the Tegalsiwalan sub-district, namely the Raudlatul Munadhirin Madrasah Ibtidaiyah. In this study, researchers collected data by means of interviews, observation and documentation. The data analysis technique used is data reduction, data presentation and data verification. In checking the validity of the findings here the researcher used two techniques namely, extended participation, and observed observation. From the results of the study it was found that (1) The use of Mother Language as a Communication Tool in learning, Its use here is very helpful for teachers and students in communicating in class where when one of the students or the teacher has difficulty conveying the meaning of the learning material, the teacher or students will use Indonesian and Madurese which are combined by the two languages. (2) The role of the mother tongue in supporting the learning process is quite effective. Through the use of the mother tongue in learning, students can find out the aims and objectives desired by the teacher when the learning process takes place. Students will understand and understand more about what the teacher means, and also the development of Indonesian students will gradually build up and also be better and organized.